Pengukuran kepuasan pelanggan terhadap kualiti perkhidmatan majlis perbandaran: kajian kes Majlis Perbandaran Ampang Jaya - Wan Rosmanira Ismail; Zalina Mohd. Ali; Nur Riza Mohd. Suradi; Rofizah Mohammad (Penerbit ukm, 2007)

(untitled)
The efficiency and effectiveness of the quality management can be evaluated through performance indicator, Q such as customer satisfaction towards the service offered by an organisation. The quality service will satisfy the customers’ need when its Q value is greater than 1.00. In this study, the Importance-Performance Analysis has also been carried out as one of the tools to improve the quality of the service. Furthermore, the Gap Analysis is done to evaluate the customer satisfaction level towards the service. Positive gap value shows that customers are satisfied with the service and vice-versa. The study of measurement of quality service was carried out in the areas governed by Majlis Perbandaran Ampang Jaya (MPAJ) while concentrating on four dimension of service; (1) Municipal Health Service, (2) Municipal Basic Amenity, (3) Municipal Safety and Wellness and (4) Municipal Cleanliness and Attractiveness. The results show that for the Municipal Health Service dimension, public facilities need to be cleaned and upgraded, the housing areas has to be disease free and cleanliness/health checks has to be done. For the Municipal Basic Amenity dimension, any damage has to be corrected immediately and to make sure that the traffic system is working well. Meanwhile for the Municipal Safety and Wellness dimension, the public telephones need to be in good condition, the safety of the residents are well maintained and the areas are free from social problems. For the Municipal Cleanliness and Attractiveness dimension, the domestic waste areas need to be well maintained